A New Z3-Graded Quantum Group - Celik, Salih (HELDERMANN VERLAG, 2017)
We introduce a Z(3)-graded version of the exterior (Grassmann) algebra with two generators. Using this object we obtain a new Z(3)-graded quantum group denoted by 0((GL) over tilde (q)(2)) and discuss some of its properties.
Keywords: Z(3)-graded exterior algebra; Z(3)-graded quantum group; Z(3)-graded Hopf algebra; Mathematics